The second rural finance project = (The World Bank in Vietnam (WB), 2003)
The Second Rural Finance Project assists the Government of Vietnam in its efforts to develop the rural economy and improve the living conditions in the rural areas. There are two project components. The first component provides a general line of credit through the Rural Development Fund (RDF II) and funds micro-finance (MLF). The first is a fund at market interest rates, available through the Bank for Development and Investment of Vietnam (BIDV) to accredited participating financial institutions (PFIs) on a short-, medium-, or long-term basis to finance rural investments of farm households and private rural entrepreneurs that are economically and technically viable. A fund lent by BIDV to MFIs at market rates would form the MLF, which will provide finance for working capital and small capital investment of micro-finances and individual poor people. This comprises the second sub-component. The second component also has two sub-components. They consist of strengthening the BIDV's financial performance, particularly increasing the quality of its loan portfolio; diversifying income sources, widening interest rate spreads, and improving operational effectiveness to increase profitability; mobilizing medium- and long-term VND resources; equity build-up; staff training; and improving management information systems and internal control systems. The second sub-component strengthens PFIs and MFIs, which institute their own respective institutional development plans